FAKTOR-FAKTOR YANG MEMENGARUHI PENERIMAAN DAN PENGGUNAAN SISTEM INFORMASI PENGELOLAAN KEUANGAN DAERAH (SIPKD) DALAM PERSPEKTIF THE UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY 2 (UTAUT 2) DI KABUPATEN SEMARANG - Sutanto, Sutanto; Ghozali, Imam; Handayani, Rr. Sri (JURNAL AKUNTANSI DAN AUDITING, 2018)
This study aims to analysis and obtain empirical evidence of factors that affected the end user’sacceptance of SIPKD in Semarang Regency by using UTAUT 2 model. Sistem InformasiPengelolaan Keuangan Daerah (SIPKD) is an integrated application as a tool of localgovernment to improve the effectiveness of the implementation of regional financial managementregulations. This application is based on efficiency, economical, effective, transparent,accountable, and auditable principles. The independent variables in this study consisted ofperformance expectancy, effort expectancy, social influence, facilitating conditions, hedonicmotivation, and habit. The dependent variable consists of behavioral intention and use behavior.The relationship between independent variables to dependent variable was moderated by age,gender, and experience.Population variable in this research is SIPKD user or operator in 46local area of Government of Semarang Regency that is 331 user of SIPKD. The technique ofdetermining the sample using proportionate stratified random sampling method so that thesample in this study as many as 207 users of SIPKD. The data used were primary data collectedusing questionnaire survey method. The hypothesis of the research was tested by using PartialLeast Squares Structural Equation Modeling (PLS-SEM) analysis with SmartPLS applicationv.3.2.7. The results showed that hedonic motivation and habit influence the behavioral intentionto use SIPKD, the higher the level of pleasure and habits of using SIPKD then the intention touse SIPKD will be stronger. Facilitating conditions, habit and behavioral intention have an effecton Use behavior. The better the conditions that facilitate, the higher the use of SIPKD, and theintention to use the stronger the higher the SIPKD usage behavior often. The results of the test ofage, gender, and experience variables showed no moderate effects on behavioral intention anduse behavior.